Comparison of Land Surface Temperature Before, During and After the Covid‑19 Lockdown Using Landsat Imagery: A Case Study of Casablanca City, Morocco - Taoufik, Meryem; Laghlimi, Meriem; Fekri, Ahmed (Geomatics and Environmental Engineering, 2021)
Land Surface Temperature (LST) is an important variable within global climate change. With the appearance of remote sensing techniques and advanced GIS software, it is now possible to estimate LST. In this study, the effect of lockdown during COVID-19 on the LST was assessed using Landsat 8 Imagery. LST dynamic was investigated for three different periods: Before, during and after the COVID-19 lockdown. The study was conducted in Casablanca City. The results showed that during the emergence of COVID-19 with lockdown policy applied, the LST decreases remarkably compared to the previous 4-years´ average LST. After the easing of restrictions, the LST increased to exceed the previous 4-year mean LST. Furthermore, throughout all studied periods, the LST recorded its higher values in industrial zones and areas with high urban density and urban transportation, which indicates the conspicuous impact of anthropogenic activities on the LST variation. These findings indicate an ability to assess the feasibility of planned lockdowns intended as a potential preventive mechanism to reduce LST peaks and the loss of air quality in metropolitan environments in the future.